THE EFFECT OF CUTANEOUS SECRETIONS OF CYPRINIDAE FISH ON PATHOGENIC BACTERIA ERYSIPELOTHRIX RHUSIOPATHIAE POPULATIONS - O. Gulay (Ribogospodarsʹka Nauka Ukraïni, 2014)
Purpose. To investigate the effect of cutaneous secretions of Cyprinidae fish on the populations of pathogenic bacteria Erysipelothrix rhusiopathiae.